1982
DOI: 10.1161/01.hyp.4.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral consequences of mild hypertension.

Abstract: SUMMARY Tests made of the sensory-perceptual, cognitive, and psychomotor abilities of untreated young patients with essential hypertension have revealed a pattern suggesting a slight functional impairment of the central nervous system. Reduced performance was most marked for those tasks requiring speed arid psychomotor coordination, particularly when the behaviors observed were self-initiated. Lowered scores were more evident among female hypertensives; no differences in performance by race were noted. The def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
0
2

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 17 publications
9
67
0
2
Order By: Relevance
“…Hypertension, due to its chronicity, may interfere directly with various aspects of the patient's life. Self-esteem can be undermined leading to negative feelings such as depression and anxiety 27 . Just the fact that the individual being labeled as hypertensive may lead them to manifestations of anxiety and insecurity.…”
Section: Mental Health (Mh)mentioning
confidence: 99%
“…Hypertension, due to its chronicity, may interfere directly with various aspects of the patient's life. Self-esteem can be undermined leading to negative feelings such as depression and anxiety 27 . Just the fact that the individual being labeled as hypertensive may lead them to manifestations of anxiety and insecurity.…”
Section: Mental Health (Mh)mentioning
confidence: 99%
“…From the 41 matched pairs of normotensives and hypertensives (82 subjects) who had been tested in the previous study, 21 we were able to retest 58 subjects, consisting of 12 normotensive men, 16 hypertensive men, 12 normotensive women, and 18 hypertensive women.…”
Section: Subjectsmentioning
confidence: 99%
“…5 Since some of these studies were conducted with highly selected subjects, 7 l8 often with small numbers, 6 " and with populations with high levels of psychopathology , 6 7 l2 16 we decided to assess a broad battery of psychological functions in a reasonably large sample of newly detected, untreated hypertensive patients and carefully matched normotensive controls. 21 Generally young and otherwise healthy, these patients were representative of early mild hypertensives in the general population. The results of this earlier study demonstrated that, even in these early and mild cases, there were significant differences in performance scores on a number of the tests -all in the direction of impaired behavioral scores in the hypertensives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only preliminary steps have been taken in this regard. For example, hypertension has been found to be associated with impairment of various parameters of brain function (99,100). In 1977, Kleinman and co-workers demonstrated that biofeedback-assisted relaxa tion could reverse some of these changes (101).…”
Section: What Is the Clinical Status Of Relaxation And Biofeedmentioning
confidence: 99%